2006
DOI: 10.1016/j.aquatox.2006.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Harmful algal bloom toxins alter c-Fos protein expression in the brain of killifish, Fundulus heteroclitus

Abstract: The immediate early gene c-fos, and its protein product c-Fos, are known to be induced in neurons of mammals and fish as a result of neuronal stimulation. The purpose of this study was to quantitatively examine CNS alterations in killifish, Fundulus heteroclitus, in relation to harmful algal bloom (HAB) toxin exposure. c-Fos expression was visualized using immunocytochemistry in the brains of killifish exposed to the excitatory neurotoxins domoic acid (DA) and brevetoxin (PbTx-2), and a paralytic neurotoxin, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…The majority of work in killifish has examined handling stress. This stressor has been shown to alter neuronal activation in the killifish brain, as demonstrated by increased expression of c-fos in various brain regions (Salierno et al, 2006), and to increase plasma cortisol, which is the primary glucocorticoid in fish (Leach and Taylor, 1980). The northern and southern subspecies of killifish differ in their susceptibility to handling stress.…”
Section: Behavioural and Biotic Stressorsmentioning
confidence: 99%
“…The majority of work in killifish has examined handling stress. This stressor has been shown to alter neuronal activation in the killifish brain, as demonstrated by increased expression of c-fos in various brain regions (Salierno et al, 2006), and to increase plasma cortisol, which is the primary glucocorticoid in fish (Leach and Taylor, 1980). The northern and southern subspecies of killifish differ in their susceptibility to handling stress.…”
Section: Behavioural and Biotic Stressorsmentioning
confidence: 99%
“…The neurological effect of harmful algal bloom toxins on the killifish Fundulus heteroclitus has been investigated (Salierno et al, 2006). In this work, induction of c-Fos, a protein biomarker for neuronal and regional brain activity, was evaluated when specimens were exposed to the excitatory neurotoxins domoic acid and brevetoxin B, and the paralytic neurotoxin saxitoxin.…”
Section: Consumer Neuroecologymentioning
confidence: 99%
“…In rainbow trout brain, the administration of kainic acid increased c-Fos mRNA expression after 60 min and for up to 120 min, at which time it then decreased towards control levels (Matsuoka et al 1998). Another study described an increased c-Fos expression in brainstem of rainbow trout following a startle response (Bosch et al 2001), and recently Salierno et al (2006) found altered c-Fos protein expression in killifish which were exposed to harmful algal bloom toxins. However, no studies to date have investigated alterations in c-Fos mRNA or protein expression in brain of fish subjected to hypercapnic stress.…”
Section: Time Points Testedmentioning
confidence: 98%